Log(x)+Log(x-1)=Log(x-2)

Simple and best practice solution for Log(x)+Log(x-1)=Log(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Log(x)+Log(x-1)=Log(x-2) equation:


Simplifying
Log(x) + Log(x + -1) = Log(x + -2)

Multiply goL * x
goxL + Log(x + -1) = Log(x + -2)

Reorder the terms:
goxL + goL(-1 + x) = Log(x + -2)
goxL + (-1 * goL + x * goL) = Log(x + -2)
goxL + (-1goL + goxL) = Log(x + -2)

Reorder the terms:
-1goL + goxL + goxL = Log(x + -2)

Combine like terms: goxL + goxL = 2goxL
-1goL + 2goxL = Log(x + -2)

Reorder the terms:
-1goL + 2goxL = goL(-2 + x)
-1goL + 2goxL = (-2 * goL + x * goL)
-1goL + 2goxL = (-2goL + goxL)

Solving
-1goL + 2goxL = -2goL + goxL

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '2goL' to each side of the equation.
-1goL + 2goL + 2goxL = -2goL + 2goL + goxL

Combine like terms: -1goL + 2goL = 1goL
1goL + 2goxL = -2goL + 2goL + goxL

Combine like terms: -2goL + 2goL = 0
1goL + 2goxL = 0 + goxL
1goL + 2goxL = goxL

Add '-1goxL' to each side of the equation.
1goL + 2goxL + -1goxL = goxL + -1goxL

Combine like terms: 2goxL + -1goxL = 1goxL
1goL + 1goxL = goxL + -1goxL

Combine like terms: goxL + -1goxL = 0
1goL + 1goxL = 0

Factor out the Greatest Common Factor (GCF), 'goL'.
goL(1 + x) = 0

Subproblem 1

Set the factor 'goL' equal to zero and attempt to solve: Simplifying goL = 0 Solving goL = 0 Move all terms containing g to the left, all other terms to the right. Simplifying goL = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing g to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Add '-1x' to each side of the equation. x + -1x = -1 + -1x Combine like terms: x + -1x = 0 0 = -1 + -1x Simplifying 0 = -1 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 4(11)-28=24 | | -14=32+x | | -54-x=48-7x | | 2y+5x=y+3x+5 | | 12+3x=18.75 | | 8H=-16(h-24) | | -56-5x=3x+16 | | 4(13)-28=24 | | -54-x=48-7 | | 4(x-8)=7(x+7)-x | | 3x+y=6x-9 | | 37-3x=15+8x | | 4x^2-9-28=0 | | f(x)=-0.01x^4-0.2x^3+0.4x^2+0.8x+3.5 | | -3x-20=30-5x | | Mx-4y=3tforx | | 7x-3=-2x+9 | | -8=-5q | | -10+7f=9f+10 | | -3.503b+3.9+3.7b=4.7865 | | 2-3t+6=17 | | 30n^2+294n+216=0 | | 18+[15-(8-1)]x-3= | | -123-2x=-9x+87 | | 2d+5=d+11 | | 6(5-4*2.33)= | | -9c+7=-10c | | -w^2-3w+10=0 | | 7x-4=143 | | -8h=-6-9h | | b-5+7b=34 | | -18-2x=5x+45 |

Equations solver categories